Multifrequency electrical impedance tomography (Mf-EIT) for the detection of breast cancer phantom anomalies - Bayu Ariwanto; Khusnul Ain; Riries Rulaningtyas; Nuril Ukhrowiyah; Rohadatul Aisya; Ahmad Hoirul Basori; Andi Besse Fidausiah Mansur (MethodsX)
Breast cancer is the most commonly diagnosed neoplasm and one of the most widespread cancers among women. The research advanced the Mf-EIT hardware through analogue discovery, component assessment, hardware integration, software creation, and data reconstruction utilizing Gauss-Newton and GREIT approaches. The breast cancer phantom consisted of a gelatin and sodium chloride solution. The position and number of anomalies in the reconstructed image correspond with the phantom. Anomalies in the reconstructed image are illustrated in red, indicating that they exhibit higher conductivity than their environment. The smallest percentage difference in conductivity between the reconstructed image of the cancer abnormality and the phantom is 0.18 %, recorded at a current of 0.35 mA and a frequency of 150 kHz. The smallest percentage difference in size between cancer abnormalities 1 and 2 in the reconstructed image and the phantom is 0.14 %, observed at a current of 0.22 mA and a frequency of 80 kHz. In brief, • This study proposes an innovative Electrical Impedance Tomography (EIT) • The designed and built the Mf-EIT hardware based on data reconstruction using Gauss-Newton and GREIT • The Electrical Impedance Tomography designed to detect the anomalies in the reconstructed image of Breast Cancer.